Universality in action: Why and how United Nations development work should engage with high-income countries - Max-Otto Baumann; Sebastian Haug (German Institute of Development and Sustainability (IDOS), 2024)
This Discussion Paper makes the case for universality in United Nations (UN) development work. So far, the UN development pillar has largely remained wedded to a 20th-century approach to development cooperation that centres on two groups of states and a one-way relationship between them: rich countries provide support to poor countries. However, the proliferation of global challenges, increasing levels of transnational interdependence, and the partial dissolution and reconfiguration of North-South dichotomies point to the need for a new rationale for international cooperation. Development-related challenges do not cease with a country's graduation to high-income status, and taming the externalities of high-income societies requires comprehensive global action. As a multilateral organisation with quasi universal reach, the UN cannot afford to ignore development processes in high-income countries if it wants to contribute to successful cross-border cooperation and strengthen the UN as a central node through which member states can effectively address global sustainability challenges. To give practical meaning to universality, the UN needs to provide intergovernmental spaces in which all states can meet on an equal footing. It needs to monitor challenges and facilitate solutions across all member states. And it needs to lead the way towards forms of global knowledge production where analysis and learning are not restricted by artificial North-South boundaries.
Keywords: 320; United Nations; 2030 Agenda; Universality; International Cooperation; Sustainable Development